Intelligent Light Communication from Automated Vehicles to Other Road Users - Karlsson, Henrik; Lidman Olsson, Anna (My University, 2019)
The development of AVs (automated vehicles) is moving rapidly and many automakers are including more and more ADAS (Advanced Driver Assistance System) in their vehicles as steps towards full autonomy. However, there are many aspects to consider before AVs can function on public roads. One important topic is how these AVs will communicate with other road users, which is what this master thesis project aims to investigate. The project is in collaboration with Volvo GTT (Group Trucks Technology) and focuses on external light communication from automated HGVs (Heavy Goods Vehicles) to other road users. A survey, answered by 111 participants, was used to investigate in what situations additional light communication is needed. Additionally, a need for AVs to be able to act assertive just as human drivers do in certain situations to help the overall traffic flow was identified. Based on this, a scenario where an HGV needs to merge from a highway on-ramp into traffic congestion was chosen for further investigation. When analysing the chosen scenario, three primary needs for additional light communication were identified: (1) communicating that the HGV has to merge, (2) communicating the urgency of the situation and (3) communicating when the HGV will initiate the turn. A concept was developed consisting of long LED-strips mounted on the cab together with a modified flash sequence of the light. The new sequence consists of three phases, the first being the same steady turn signal used today. In the second phase, the light flashes in a double pattern, similar to a heartbeat, to communicate urgency. In the third phase, which is activated just before the turn is initiated, the light flashes with higher frequency to catch even more attention from the other road users. The concept was tested using a VR-simulation of the chosen scenario where eleven participants drove a passenger vehicle and had to interact with a merging HGV equipped with the proposed concept. The evaluation confirmed the hypothesis that the larger LED-strips attracted more attention than traditional turn signals. When interviewed about the new flash sequences, the majority of the participants understood its meaning and thought that it would help an AV to communicate the urgency of the situation.
Keywords: automated vehicle; heavy goods vehicle; turn signal; road users; visual communication; external communication